Legal Problems of Gold-Indexed Land Pawn Practices in the Perspective of Islamic Economic Law: An Empirical Study in Tlonto Ares Village, Pamekasan Regency - Rian Hidayatullah; Mohammad Mahmudi (Journal of Indonesian Islamic Studies, 2026)
This study examines the practice of gold-indexed land pawning in Tlonto Ares Village, Pamekasan Regency, and analyzes its compatibility with the principles of Islamic Economic Law. The study addresses an important gap in the literature, as existing research on land pawn transactions has primarily focused on collateral utilization and the general legality of rahn, while limited attention has been given to gold-based debt valuation in rural community transactions. This research employs an empirical legal method with a qualitative socio-juridical approach. Data were collected through observation, in-depth interviews, and documentation involving pledgors (rahin), pledge holders (murtahin), religious leaders, community figures, and village officials. The findings reveal that land is used as collateral, while the debt value is converted into a specific quantity of gold at the time of contract formation and repayment is adjusted according to prevailing gold prices at redemption. During the contract period, the pledge holder also retains control over and benefits from the pledged land. The study identifies a dual-benefit structure in which the pledge holder gains both economic protection through gold indexation and additional benefits from land utilization. From the perspective of Islamic Economic Law, this practice partially supports the objective of wealth protection (ḥifẓ al-māl) by preserving the real value of debt. However, it also raises significant concerns regarding riba, gharar, contractual imbalance, and potential economic exploitation. Viewed through the framework of maqāṣid al-sharī‘ah, the practice reflects a tension between wealth protection and the realization of justice (al-‘adālah) and public welfare (maslahah). This study contributes to Islamic Economic Law scholarship by demonstrating that the legal assessment of community-based pawn transactions must extend beyond formal contractual validity to include substantive justice, proportional benefit distribution, and broader socio-economic welfare.